2011
DOI: 10.1186/1471-2407-11-406
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacogenomic testing of KRAS, BRAF and EGFRmutations by high resolution melting analysis and ultra-deep pyrosequencing

Abstract: BackgroundEpidermal growth factor receptor (EGFR) and its downstream factors KRAS and BRAF are mutated in several types of cancer, affecting the clinical response to EGFR inhibitors. Mutations in the EGFR kinase domain predict sensitivity to the tyrosine kinase inhibitors gefitinib and erlotinib in lung adenocarcinoma, while activating point mutations in KRAS and BRAF confer resistance to the anti-EGFR monoclonal antibody cetuximab in colorectal cancer. The development of new generation methods for systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 26 publications
3
65
1
1
Order By: Relevance
“…Although, we did not compare pyrosequencing with other methods, pyrosequencing method is sensitive in detecting both EGFR and KRAS mutations. Similar to previous reports, EGFR mutations were prevalent in nonsmokers (65.43%, P < 0.001), whereas KRAS mutations were common in smokers (67.85%, P < 0.001), and the two mutations are mutually exclusive in our study (6)(7)(8)25,29).…”
Section: Discussionsupporting
confidence: 79%
“…Although, we did not compare pyrosequencing with other methods, pyrosequencing method is sensitive in detecting both EGFR and KRAS mutations. Similar to previous reports, EGFR mutations were prevalent in nonsmokers (65.43%, P < 0.001), whereas KRAS mutations were common in smokers (67.85%, P < 0.001), and the two mutations are mutually exclusive in our study (6)(7)(8)25,29).…”
Section: Discussionsupporting
confidence: 79%
“…It was reported that LNA-based PCR clamping was able to detect 1% mutated KRAS in the template composite (26). Regarding HRM, KRAS mutations at a ratio of 5% were necessary to be detectable (27,28). A related method, the Digital Melt Curve (DMC) assay, was conducted as a two-step method enriching target genes by sequence-specific capture before combined digital PCR and HRM (29).…”
Section: Discussionmentioning
confidence: 99%
“…We may speculate that this patient had greater-than-usual benefit from biological treatment. Although some studies have reported cases of double mutants, they always involved combination one activating mutation and one resistance mutation [35,40]. Double mutants are usually only found in cell lines, especially substitutions in exon 21 (p.L858R) and in exon 20 (p.T790M).…”
Section: Discussionmentioning
confidence: 99%